Acceleration time, peak torque and time to peak torque in elite karate athletes - Scattone-Silva, R.; Lessi, G.C.; Lobato, D.F.M.; Serrão, F.V. (Science & Sports, 2012)
Aim To assess the bilateral differences in peak torque normalized by the body mass (PT/BM), acceleration time (AcT) and time to peak torque of the knee and elbow muscles of elite karate athletes, in order to identify risk factors for injury. Methods Seven male elite karate competitive athletes were evaluated in an isokinetic dynamometer at 60°/s and 360°/s. Results No bilateral difference was found in any of the variables on the knee flexion and extension assessment (P > 0.05). The elbow assessment revealed higher values of PT/BM in elbow flexion (P = 0.02) and a smaller AcT in elbow extension (P = 0.01) at the 60°/s speed on the dominant limb when compared to the non-dominant limb. At the 360°/s speed, the non-dominant elbow presented a smaller AcT in elbow extension when compared to the dominant limb (P = 0.05). Moreover, the data regarding the flexor/extensor ratio on both joints revealed values that have been related to an increased risk of joint injury in young athletes. Conclusion Our results indicate that the functional demands of regular competitive karate training are not necessarily bilateral strength differences induced-factors in male karate elite athletes, especially considering that similar bilateral differences were found previously in healthy non-athletes. However, the competitive regular training of this martial art could produce agonist-antagonist muscle asymmetries that could predispose these athletes to injuries in the elbow and knee joints.